A Variant of Poland’s syndrome - Case Report and Review of Literature - Rauniyar, RK; Baboo, S; Sharma, U; Garg, M (Nepalese Journal of Radiology, 2012)
Poland’s syndrome is the association of congenital thoracic abnormalities with ipsilateral syndactyly along with various other associated anomalies. A variant of Poland’s syndrome without syndactyly along with review of literature is presented here. Various associated anomalies of the syndrome is summarized. Syndactyly believed to be constant features in Poland’s Syndrome in earlier reports, may not be present. DOI: http://dx.doi.org/10.3126/njr.v1i1.6328 Nepalese Journal of Radiology Vol.1(1): 65-69